Co-benefits of resilience planning: a review of analysis tools and methods - Helgeson, Jennifer F.; Al Kajbaf, Azin; Fung, Juan F. (Frontiers in Climate, 2025)
Co-benefits conceptually apply broadly to the realms of sustainability and resilience and are increasingly relevant in decision-making processes as there is an increase in complex and compound events. Therefore, infrastructure design, planning, governance, and disaster preparedness for compound events are critical for building resilient systems. Decisions are often based on direct benefits of a proposed project or intervention, which are the more salient to decision makers and may be the function of available financing and experience with event types. The ideal community resilience actions for a community may be heavily influenced by the identification (and inclusion) of co-benefits in assessments of community resilience alternatives. Fung and Helgeson reviewed the literature on co-benefits with a specific focus on the definition of co-benefits, areas where co-benefits are used the most (considering the literature related to climate change), and co-benefit measurement and assessment methodologies in the context of resilience planning. The current study further explores these areas by focusing on the development of the literature on co-benefits published since 2017. The specific review questions explored are: (1) What is the major focus of the literature on co-benefits? and (2) What are methods and tools for measurement and assessment of co-benefits? The literature review reveals two primary focus areas: co-benefits of resilience and sustainability planning, and co-benefits of climate mitigation and adaptation actions. The latter are further categorized as falling as either health co-benefits or environmental and social co-benefits of climate actions. Within the two broad focus areas, our study reviews research objectives, analysis region, co-benefit categories, direct benefits, and evaluation methods and assessment frameworks. Moreover, we provide a synthesis of analysis tools and assessment methods including monetization methods, multi-criteria (i.e., multi-objective) analysis methods, scoring methods and matrices, and systematic reviews. The review reveals several gaps and opportunities for both future research and applications. One opportunity is to develop more generic evaluation methods for co-benefits with a focus on scoring methods and matrices, which provide a good balance of quantitative and qualitative evaluation, in the development of more generic analysis and assessment methods and tools.